Lower lip squamous cell carcinoma: a case report of surgical treatment with reconstruction using a bilateral Bernard-Webster flap - Rosen B. TSOLOV; Georgi Y. YORDANOV (Archives of the Balkan Medical Union, 2020)
Introduction. Although squamous cell carcinoma (SCC) is the most common oral cancer with distribution worldwide, the giant form of the disease is extremely rare, due to its easy detection and early diagnosis. The primary goal in tumor surgery is excision with borders clear of neoplasia. The second goal is aesthetics and function retention. The specific surgical approach is chosen according to the length, the thickness and the location of the lip defect.